Capillaroscopic patterns in patients with systemic sclerosis, psoriasis and alopecia and their correlations with serum concentrations of several angiogenic markers - Chodorowska, Grażyna; Michalska-Jakubus, Małgorzata; Bartosińska, Joanna; Gerkowicz, Agnieszka; Adamczyk, Michał; Krasowska, Dorota (Polish Journal of Public Health, 2015)
Introduction. Capillaroscopy is a non-invasive imaging method that allows cutaneous microcirculation to be analyzed. During the last decades, a diagnostic and prognostic potential of nailfold capillaroscopy (NVC) has been gaining increasing appreciation. The main indications include Raynaud phenomenon and scleroderma spectrum diseases, however the usefulness of this technique is also suggested in a variety of non-rheumatic diseases.Aim. To assess capillaroscopic patterns in systemic scleroderma (SSc), psoriasis (PV), psoriatic arthritis (PsA), alopecia areata (AA) and androgenetic alopecia. To evaluate serum levels of several endothelial and angiogenic markers, and their relation to capillaroscopic pattern.Material and methods. There were evaluated 295 patients with systemic scleroderma (SSc), psoriasis (PV), psoriatic arthritis (PsA), alopecia areata (AA) and androgenetic alopecia, as well as age- and sex-matched controls, were examined. In each subject, NVC was performed and serum concentration levels of several angiogenic markers.Results. In SSc three NVC patterns: early, active and late were distinguished. Angiopoietin-2 concentrations were higher and andothelial microparticles were lower in patients with late NVC pattern. We found several differences between the NVC pattern in PV and PsA. No correlations between NVC pattern and serum levels of angiogenic markers were revealed. In AA, we distinguished both normal and abnormal NVC patterns, although the normal patterns were more frequent. Branching capillaries and features of neoformation were often present in patients with the abnormal pattern. In androgenetic alopecia, the normal NVC pattern was most frequently present, however, we found several statistically significant capillarosopic alterations, like branching capillaries, features of neoformation and altered distribution of capillaries.Discussion and Conclusions. Serum levels of Ang-2 and EMPs may reflect capillary damage in SSc. NVC pattern varies between PV and PsA patients. The presence of abnormal NVC patterns in alopecia patients might show the role of disturbances in microcirculation in the diseases. Further studies are required to confirm the hypothesis.